Fake News and Vaccine Hesitancy in Ijebu-Ode LGA, Ogun State: Assessing the Role of Misinformation in Public Health Decision-Making - Akinrinola, Daniel Gbolahan; Adedeji, Odunayo Christianah (NIU Journal of Social Sciences; Vol 11 No 1 (2025): NIU Journal of Social Sciences, Vol. 11 No. 1, March 2025, 2025)
This study explores the impact of vaccine misinformation on vaccine hesitancy and refusal in Ijebu-Ode LGA, Ogun State, Nigeria, using the Health Belief Model (HBM) as a theoretical framework. The research employed a quantitative approach, surveying 384 respondents with a structured questionnaire to examine the prevalence, sources, and effects of vaccine misinformation. Findings reveal that social media (72.4%) and word of mouth (58.1%) are the most common sources of misinformation, significantly influencing vaccine hesitancy (56.8%) and (59.4) refusal.  30.7% of the respondents are indifferent about the effectiveness of government and public health responses to vaccine misinformation. However, 21.4% respondents perceive public health responses as somewhat ineffective and 25.5% consider the government and public health efforts to be somewhat effective, suggesting a need for stronger intervention strategies. Recommendations include the enhancement of public awareness campaigns, fact-checking initiatives, and the involvement of community leaders to combat misinformation. Strengthening social media regulations and offering vaccination incentives were also suggested. In conclusion, addressing vaccine misinformation through targeted communication and policy strategies is crucial for improving vaccine acceptance, enhancing public health outcomes, and achieving herd immunity in Ijebu-Ode LGA Keyword: Fake news, Misinformation, Vaccine hesitance, Ijebu-Ode, Public health